Yahudi di Indonesia: Analisis Interpretasi Nawawi al-Bantani dalam Kitab Marāḥ Labīd - Muhammad Muhammad (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Jews in Indonesia: An Analyst of the Interpretation of Jewish Verses in the Book of Marāḥ Labīh by Nawawi al-BantaniThe work of interpretation of the Qur'an is one of the writings that has had a major influence on the formation of the ideology of the world's Muslims. Indonesia with a Muslim majority community also experiences this. Indonesia has many credible Muslim scholars in various fields, one of which is in the interpretation of the Qur'an. Nawawi al-Bantani is one of the Indonesian Muslim scholars who is engaged in the study of the interpretation of the Qur'an. The book of Marāḥ Labīh is a concrete proof. This article aims to examine Nawawi's interpretation when dealing with Jewish verses in the Qur'an. The descriptive-analytic method is used as a step to solve the existing problems. The results of this study indicate that Nawawi al-Bantani's interpretation of Marāḥ Labīh is anti-Semitic even though Nawawi did not contextualize his interpretation of the Jews of his time. The character and character of the Jews are expressed clearly and with determination, only a few Jews realize their mistakes